2020
DOI: 10.3390/md18060324
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Polyketides from a Symbiotic Strain Aspergillus fumigatus D and Characterization of Their Biosynthetic Gene D8.t287

Abstract: The chemical investigation of one symbiotic strain, Aspergillus fumigatus D, from the coastal plant Edgeworthia chrysantha Lindl led to the isolation of eight compounds (1–8), which were respectively identified as rubrofusarin B (1), alternariol 9-O-methyl ether (2), fonsecinone D (3), asperpyrone A (4), asperpyrone D (5), fonsecinone B (6), fonsecinone A (7), and aurasperone A (8) by a combination of spectroscopic methods (1D NMR and ESI-MS) as well as by comparison with the literature data. An antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Crystallization of the title compound in CHCl 2 -N-hexane (6:1, v/v) gave yellow crystals at room temperature. It has been reported that this compound displayed antibacterial activity against C. Albi-cans and Escherichia coli, and shown to be cytotoxic to the colon cancer cell line SW1116 [5][6][7][8][9]. What's more, the X-ray crystallography data of the title compound are reported here for the first time.…”
Section: Commentmentioning
confidence: 68%
“…Crystallization of the title compound in CHCl 2 -N-hexane (6:1, v/v) gave yellow crystals at room temperature. It has been reported that this compound displayed antibacterial activity against C. Albi-cans and Escherichia coli, and shown to be cytotoxic to the colon cancer cell line SW1116 [5][6][7][8][9]. What's more, the X-ray crystallography data of the title compound are reported here for the first time.…”
Section: Commentmentioning
confidence: 68%
“…Biosynthetically, naphtho- γ -pyrone monomers rubrofusarin B and flavasperone are aromatic polyketides, which are formed by one acetyl-CoA and six malonyl-CoA through assembly reaction catalyzed by polyketide synthase (PKS), followed by condensation, cyclization, dehydration and methylation [ 15 , 27 ]. Compound 2 is the dimerization product of two molecules of rubrofusarin B at C-7 and C-10, respectively, and it has been shown to be catalyzed by the pre-anthraquinone-dimerizing cytochrome P450 (CYP) enzyme encoded by the gene aunB [ 28 ] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we report the isolation, structural elucidation and anti-Helicobacter pylori effects of two dimeric naphtho-γ-pyrones, namely fonsecinone A (1) and isoaurasperone A (2) (Figure 1). As a structurally unique metabolite, compound 1 was first isolated from A. fonsecaeus in 1984 [13], as well as from A. aculeatus [14], A. fumigatus [15] and Pleurotus ostreatus [16] more recently, while compound 2 was obtained from A. niger in 1979 for the first time and it exhibited cytotoxic and mycotoxic properties [17]. However, the compounds' stereochemistry has Molecules 2021, 26, 5061 2 of 8 not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these monomers further dimerized at various carbon positions (C-6, C-7, C-9, or C-10) and resulted in the formation of dimers 16, 21, 27, and 28. Lately, one nrPKS gene D8.t287 responsible for the biosynthesis of the initial precursor heptaketone was identified and characterized by target gene knockout experiment and UPLC-MS analysis (Hua et al, 2020). However, the role of the gene AunB or BfoB is not confirmed so far.…”
Section: C-naphthylpyradone Dimersmentioning
confidence: 99%